Molecular biology education in Indonesia - suggestions for improvement - Wolfgang Nellen; Atika Hanoum Rahasta; Feri Eko Hermanto; Margareth Rika Wahyusari Gabriella Lorenza (The East Java Biological Society, 2017)
Education in molecular biology is considered difficult because it is complex and requires a lot of basic knowledge. Focused on basic science facts, it is usually taught with little connection to everyday life. A second problem is that the topic is rather abstract and results are only indirectly observed: we know that DNA is a double helix - but nobody has seen it directly. In contrast to subjects in the humanities and social sciences, molecular biology is a handy-craft where sophisticated theory and practical lab-work go hand in hand. Molecular biology is not so much a specific sub-discipline of biosciences but rather a huge tool box which is indispensable for all other fields of biology. It is therefore absolutely required for all biologists to know the basics and the potential of molecular biology in their specific field of interest. We present some thoughts how to make the theory more attractive, how to combine learning, training and teaching of theory and practice, how to stimulate independent, critical thinking in students and final-ly, how to identify and support excellent students who should advance science in the next generation. Last not least, we emphasize the necessity to expand information and teaching of molecular biology to the public.